2018
DOI: 10.1002/adma.201704749
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Stability and Passivation of Black Phosphorus

Abstract: From a fundamental science perspective, black phosphorus (BP) is a canonical example of a material that possesses fascinating surface and electronic properties. It has extraordinary in-plane anisotropic electrical, optical, and vibrational states, as well as a tunable band gap. However, instability of the surface due to chemical degradation in ambient conditions remains a major impediment to its prospective applications. Early studies were limited by the degradation of black phosphorous surfaces in air. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
194
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(196 citation statements)
references
References 102 publications
0
194
1
1
Order By: Relevance
“…It has been shown that all the allotropic forms of phosphorus,i ncluding the crystalline ones,c an react with O 2 and H 2 Oi nt he air to form phosphorus oxides,p hosphoric acid or phosphine gas. [53,54] RP also reacts with I 2 at moderate temperature. [53] Materials that only work under controlled conditions have limited applications.T op revent these reactions,various methods have been used to improve the stability of materials in air.F or instance,J eong et al [55] have used thermal etching to generate an oxide layer on BP,w hich stabilizes the material.…”
Section: Angewandte Chemiementioning
confidence: 97%
See 2 more Smart Citations
“…It has been shown that all the allotropic forms of phosphorus,i ncluding the crystalline ones,c an react with O 2 and H 2 Oi nt he air to form phosphorus oxides,p hosphoric acid or phosphine gas. [53,54] RP also reacts with I 2 at moderate temperature. [53] Materials that only work under controlled conditions have limited applications.T op revent these reactions,various methods have been used to improve the stability of materials in air.F or instance,J eong et al [55] have used thermal etching to generate an oxide layer on BP,w hich stabilizes the material.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…[53,54] RP also reacts with I 2 at moderate temperature. [53] Materials that only work under controlled conditions have limited applications.T op revent these reactions,various methods have been used to improve the stability of materials in air.F or instance,J eong et al [55] have used thermal etching to generate an oxide layer on BP,w hich stabilizes the material. Such approach was not successful when applied to our a-RP films as moisture was absorbed by the films,g enerating phosphoric acid (See Figure S6).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Of the group V elements, air stability remains a common issue. Phosphorene, the puckered or “black” phase, for instance, has been extensively investigated but remains highly susceptible to oxidation in air, making encapsulation schemes necessary . Meanwhile, antimonene crystals with buckled structure have been shown to be stable in air and chemically robust .…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%
“…Phosphorene, the puckered or "black" phase, for instance, has been extensively investigated but remains highly susceptible to oxidation in air, making encapsulation schemes necessary. [47][48][49] Meanwhile, antimonene crystals with buckled structure have been shown to be stable in air and chemically robust. [50] In addition, crystal forms of antimonene have been predicted to have different degrees of anisotropy in mechanical properties.…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%